Real-time SSVEP measurements through Lock-in detection in FPGA-based platform - Oliva, Matías Javier (2023)
In this work, a method for measuring steady-state visually evoked potentials using the Lock-In technique is presented. The proposed method in- volves acquiring the electroencephalography signal through channel averaging from an ADS1299 sigma-delta converter, without the need for additional hardware to accommodate the signal and processing in real-time using an Intel MAX10 FPGA, while visual stimuli synchronized with the sampling and pro- cessing are generated. The result is a robust platform that allows determining a user's attention focus on visual stimuli flickering at 14.70, 16.67, and 19.23 Hz. The initial experimental tests of the system with three subjects validated the platform, obtaining an average signal-to-noise ratio of 3.2 in the detection, with a maximum of 6.2 in the case of an experienced SSVEP user.